Pengembangan Model Pembelajaran Berbasis Kurikulum Cinta untuk Pendidikan Karakter di Madrasah Ibtidaiyah Sabang: Development of a Love Curriculum-Based Learning Model for Character Education at Sabang Elementary School - Asmita Wulan Sulastri; Muhammad Iqbal; Zikrur Rahmat (ITScience (Information Technology and Science), 2026)
This research is driven by the gap between the Love-Based Curriculum paradigm—which highlights mercy, empathy, manners, and compassion—and classroom learning practices, which remain confined to cognitive outcomes. This gap hinders effective character education, especially in Madrasah Ibtidaiyah settings. This study seeks to design a structured, applicable, and contextually relevant Love-Based Curriculum Learning Model and to evaluate its validity, practicality, and effectiveness in enhancing character education among students at Sabang State Madrasah Ibtidaiyah. The research employs a Research and Development (R&D) approach using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. Participants included teachers and students, and data were gathered through observation, interviews, questionnaires, and documentation. Study findings show the model is valid (average score: 84%), practical (85% for learning syntax, 88% for teacher response), and effective, as evidenced by an increase in student character from 66% to 86%. The model weaves mercy, empathy, manners, and local wisdom into learning syntax through empathy-driven introductions, experiential exploration, value reflection, and character reinforcement. Consequently, this model demonstrably enhances character education and is recommended as an alternative instructional method in madrasas.